New taxa of the tribe Meconematini from South-Pacific and Indo-Malayan Regions (Orthoptera, Tettigoniidae, Meconematinae) - Jin, Xingbao; Liu, Xianwei; Wang, Hanqiang (Zootaxa, 2020)
New materials of the tribe Meconematini from Southeast Asia, Indo-Malayan and South Pacific region are examined. Systematic situation of the tribe is briefly discussed. Taxonomic comments, notes, and distribution pattern on related taxa and descriptions of new species are given. Totally 73 species involving 21 genera are recognized, in which 22 species referring 11 genera are new to science, 45 species are known, including 1 genus and 1 species with new status, 3 new descriptions of another sex, 2 new synonyms and 9 species with new combinations. New species, status and combinations are as follows: